PREDICTIONS TO STOP SMOKING OF PATIENTS AFTER CARDIOVASCULAR SURGERY - EŞREF KARASU, VELİ; ÖZDEMİR, Aysun (Göbeklitepe Medical Science Journal, 2024)
This study was conducted to examine the predictions of smoking cessation success of patients who smoke after cardiovascular surgery. Cross-sectional research Dr. The study was conducted with 92 patients who applied to the cardiothoracic surgery outpatient clinic of Ersin Arslan Training and Research Hospital for control purposes. Research data were collected between 20.09.2021 and 20.03.2022 with participant introduction form and Smoking Cessation Success Prediction Scale. Mann-Whitney U, Kruskal-Wallis and regression tests were used to evaluate the data. Necessary permissions were obtained to conduct the research. For all patients participating in the study, it was found that the total mean score of the Prediction Scale for Smoking Cessation Success was 39.47±5.48, the mean of Persistence and Readiness sub-dimension score was 22.34±2.94, and the mean of Health Perception and Appropriate Environment sub-dimension was 17.13±2.96. A significant difference was determined between the predictive score averages of smoking cessation success according to the age of starting smoking and the duration of smoking (F=9.662, p<0.001). It was determined that the predictive level of smoking cessation success in cardiovascular patients was above the average. The decrease in the smoking duration of the patients positively affects the predictive level of smoking cessation success.